A Cross Sectional Study of Medical Students’ Perception of Their Educational Environment in Ghana (Journal of Education and Development, 2019)
Background: The quality of medical education is affected by many factors, one of which is the educational environment of medical education. However, there is paucity of studies addressing the educational environment from African medical schools. The aim of this study was to determine the clinical year students’ perceptions of their educational environment at a medical school in Ghana. This was done with the goal of identifying factors that may impact positive changes in the school. Methods: A cross-sectional study was undertaken using the DREEM questionnaire. The questionnaire was administered to students in clinical years 1, 2, & 3 at the time of the study. 298 students participated in the study by convenience sampling. Data was analyzed using SPSS version 24. The total score and the five subscales of DREEM scores were used in the final analysis. Results: A total of 298 out of 300 students completed the questionnaire out of which Fifty six percent of respondents were male. There was no significant gender differences in the total DREEM scores [F = 1.019, (1, 274) p=0.314]. The overall educational environment was positive M=117.32 ± 15.45. Areas for improvement were students’ perception of the teachers (26.09 ± 3.59) and students’ perception of the atmosphere (25.71 ± 5.62). The students’ perception of learning (30.70 ± 5.20), and students’ academic self-perceptions (21.11 ± 3.74) were positive. Students’ social self-perceptions (13.71 ± 2.99) was neutral. There was no significant difference in perception by clinical year [F = 0.298, p = 0.742]. (2, 274) Conclusion: The perception of students at this Ghanaian medical school can be described as positive and negative. The school should consider the two domains with negative perceptions as areas for improvement. Students reported problem-based learning as a preferred method of teaching versus the traditional method. Attention to the learning atmosphere and student-focused learning is likely to increase perception.